1999
DOI: 10.1002/(sici)1521-3862(199910)5:5<219::aid-cvde219>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Co-deposition of Silica, Alumina, and Aluminosilicates from Mixtures of CH3SiCl3, AlCl3, CO2, and H2. Thermodynamic Analysis and Experimental Kinetics Investigation

Abstract: The co-deposition of silica, alumina, and aluminosilicates from mixtures of methyltrichlorosilane, aluminum trichloride, carbon dioxide, and hydrogen was investigated in this study. In order to elucidate some aspects of the co-deposition process, the deposition of pure silica and pure alumina from mixtures of methyltrichlorosilane and aluminum trichloride, respectively, with CO 2 and H 2 was also investigated. Kinetic data were obtained by carrying out CVD experiments on SiC substrates in a hot-wall reactor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…In a previous study, 22 we investigated the chemical vapor codeposition of SiO 2 , Al 2 O 3 , and aluminosilicates from mixtures of CH 3 SiCl 3 (methyltrichlorosilane, MTS), AlCl 3 , CO 2 , and H 2 . MTS was used as silicon source because preliminary experiments showed that the rates of deposition of silica and alumina from H 2 -CO 2 mixtures containing MTS and AlCl 3 , respectively, were of comparable magnitude for similar chloride concentrations, whereas mixtures of SiCl 4 , CO 2 , and H 2 gave much lower rates of deposition of silica.…”
mentioning
confidence: 99%
“…In a previous study, 22 we investigated the chemical vapor codeposition of SiO 2 , Al 2 O 3 , and aluminosilicates from mixtures of CH 3 SiCl 3 (methyltrichlorosilane, MTS), AlCl 3 , CO 2 , and H 2 . MTS was used as silicon source because preliminary experiments showed that the rates of deposition of silica and alumina from H 2 -CO 2 mixtures containing MTS and AlCl 3 , respectively, were of comparable magnitude for similar chloride concentrations, whereas mixtures of SiCl 4 , CO 2 , and H 2 gave much lower rates of deposition of silica.…”
mentioning
confidence: 99%
“…Here it is to be considered that in a typical MCVD system, residence time at hot zone is about 0.1 second which is sufficient enough for 100% conversion of SiCl 4 to SiO 2 at temperature above 1500°C. Moreover, co-deposition of silica and alumina lowers the conversion efficiency of AlCl 3 further as reported by Nitodas et al 28 31,32 Moreover, all the aluminosilicate phases convert to mullite and cristobalite in the temperature range of 1335-1625°C. 33 So, in this study possible crystal phases that can be present are a-Al 2 O 3 , cristobalite, and mullite.…”
Section: Methodsmentioning
confidence: 58%
“…Here it is to be considered that in a typical MCVD system, residence time at hot zone is about 0.1 second which is sufficient enough for 100% conversion of SiCl 4 to SiO 2 at temperature above 1500°C. Moreover, co‐deposition of silica and alumina lowers the conversion efficiency of AlCl 3 further as reported by Nitodas et al . Around 1100°C, conversion of AlCl 3 to Al 2 O 3 merely starts, whereas SiCl 4 almost completely converts to SiO 2 at this point.…”
Section: Resultsmentioning
confidence: 99%
“…The increase resulted in the formation of a very Al 2 O 3rich mullite and has been described by other authors. 10,11 (…”
Section: (1) Effect Of H 2 :Co 2 Feed Rate On Coating Composition Andmentioning
confidence: 99%
“…Nitodas and Sotirchos 10,11 report thermodynamic analysis and kinetics data for CVD of Al 2 O 3 , SiO 2 , and Al 2 O 3 -SiO 2 for CH 3 SiCl 3 (g), AlCl 3 (g), CO 2 (g), and H 2 (g) as the reactants. Their observation of suppressed Al 2 O 3 deposition during Al 2 O 3 -SiO 2 codeposition as the amount of CO 2 (g) increases is consistent with their thermodynamic calculations, which show a decrease in the concentration of aluminum-containing gaseous species as the amount of CO 2 (g) increases.…”
Section: Introductionmentioning
confidence: 99%